AL-USUS AL-TSAQAFIYAH LI I’DADI MAWAD TA’LIM AL-LUGHAH AL-’ARABIYAH - Fu'adah, Shofwatul; Almannah Wassalwa; Irfan; Ahmadi M (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
Language is the vessel of culture and is the primary means of expressing it in many fields. The Arabic language and its culture go hand in hand. It is difficult for a foreign student to understand the Arabic language accurately or to use it well without understanding the specific cultural concepts associated with it. The idea of ​​teaching the cultural content of the language comes first, not for cultural purposes, but for linguistic purposes. Literature review is a research methodology used in this study. When creating teaching materials, researchers collect information from textual and electronic publications regarding sociocultural concepts. The result of the study aims to discusses culture and its characteristics, the relationship between language and culture, culture and learning Arabic for non-Arabs as well as cultural content in teaching Arabic as a foreign language, especially things that need to be considered in the cultural aspect when preparing Arabic language teaching books for foreign students. Therefore, paying attention to the cultural foundations when preparing books for teaching the Arabic language to non-native speakers is important for achieving the goals of teaching the Arabic language. Every teacher must take into account the specific matters that must be taken into account when preparing books for teaching the Arabic language to foreigners so that it suits the learner’s linguistic and mental level.